Performance of the Security Intelligence Unit in Early Detection to Control Kamtibmas Disturbances in Brebes Police Jurisdiction - Setiawan, Rino (Advances in Police Science Research Journal, 2024)
Overcoming the crime rate is an exciting social problem both globally and in Indonesia because this is related to the level of people’s welfare, as we all know that Indonesia is a country with a very large number of workers. Then, the purpose of this study is to thoroughly describe how the performance of the Brebes Police’s satintelkam and problem-solving steps that can improve the performance of satintelkam’s performance in early detection so that it complies with the rules and regulations as appropriate. The method used is a qualitative approach and focuses on problems related to early detection in order to control kamtibmas disturbances in the jurisdiction of the Brebes Regional Police. Data sources were obtained through observation, interviews, and document review from Satintelkam and other agencies and Kamtibmas. Validity is carried out on each data obtained and analyzes the data to get conclusions. The conceptuals used include the concept of intelligence, the concept of performance, the concept of early detection, the concept of control, the concept of Kamtibmas Interference. The theory used is the POAC management theory Early detection for control of kamtibmas disorders has not been carried out properly due to several problems. These problems include personnel, budget, facilities and infrastructure, intelligence products, and the implementation of early detection Method according to the Standard Operating Procedures (SOP) used. Through factual conditions, the author analyzes the ideal conditions to get a solution to the problem. Through this discussion, the performance of security intelligence units needs to improve organizational resources so that they can be maximized and early detection Method that are in accordance with applicable rules and SOPs.